Main drivers in the structure and dynamics of the zooplankton community in a pampean seepage shallow lake throughout an annual cycle during turbid and clear water regimes - Ardohain, Diego Martin (2021)
We investigated the composition and dynamics of the zooplankton community in a pampean seepage lake (Buenos Aires, Argentina) under different environmental (rainfall, hydrometric level, conductivity, transparency) and biotic (phytoplankton biomass and presence of submerged macrophytes) conditions. In the annual cycle analyzed, the shallow lake evidenced alternating turbid- and clear-water periods associated with changes in phytoplankton biomass and the extent of colonization by submerged macrophytes. Thirty-five species were identified (21 rotifers, nine cladocerans and five copepods). Only six species were perennial: the rotifers Brachionus caudatus, Keratella tropica; the cladoceran Ceriodaphnia dubia; and the copepods Notodiaptomus incompositus, Metacyclops mendocinus, and Microcyclops dubitabilis. The zooplankton manifested a similar annual-abundance pattern in the three sampling stations established. Density and biomass peaks occurred in autumn during the clear phase without submerged macrophytes, whereas minimum values were obtained during the turbid phase. The presence of submerged macrophytes favored the zooplankton community, as evidenced by an increased abundance (twice that recorded during the turbid period) and species richness (from 20 to 30 species), with both parameters being associated with increased possibilities for zooplankton refuge plus an incorporation of periphytic and benthic species. Rotifers always predominated numerically. The copepod contribution prevailed throughout the annual cycle with respect to biomass except in spring when the cladocerans were more prevalent. These findings demonstrated that the zooplankton community responded positively to the changes that occurred in the environmental conditions of the lake between the turbid- and the clear-water states.